PENGARUH FAKTOR SOSIAL DAN FAKTOR BUDAYA TERHADAP KEPUTUSAN PEMBELIAN PRODUK ES TEH TALI PINGGIR UNSIKA - Widari Widari; Ajat Sudrajat (Institut Teknologi dan Bisnis Dewantara, 2025)
This study aims to analyze how social variables, such as reference group, family, and social roles & status, as well as cultural elements, including cultural and subcultural influences, affect the purchasing decision of the product Ice Tea Ribbon Edge at the University of Singapore (UNSIKA. The study utilizes primary data collected by distributing questionnaires to students of UNSIKA and the general population. The research findings indicate that social elements, including reference groups, families, as well as social roles and status, exert a substantial impact on the purchasing choice of the goods. These findings suggest that marketers must now include social and cultural variables as essential elements in developing successful marketing strategies to boost sales of UNSIKA's Ice Tea Ribbon products.